Women in health: Social practices in online health information management - Rizghina Ikhwan (Masyarakat, Kebudayaan dan Politik, 2020)
Women have the right to take health measures on their bodies. In carrying out health measures, individuals need to seek health information. Health information can be obtained from the environment such as family, neighborhood, and groups involved in it. Along with the increase in technology, information is obtained from the individual environment and the outside world through electronic media and information spread in electronic media can be accessed anytime and anywhere. One of the groups seeking information about health from electronic media is PKK Gunung Anyar Tambak. This study used a qualitative method by conducting in-depth interviews with 16 members of the PKK Gunung Anyar Tambak using snowball sampling. This study found that the information conveyed by women was considered correct after carrying out the information management process with other people, so it requires a negotiation process when taking health measures for their families. In this case, negotiations were carried out with each of the husbands of PKK Gunung Anyar Tambak members. The husband has the power to reject or accept the information conveyed by the wife. The wife must manage online health information obtained from electronic media before it is conveyed to her husband and it can be accepted and practiced in her family.